DSFC Education on Knowledge And Attitude To Prevent Diabetic Foot Ulcer - Jamaluddin, Ahmad; Wahdaniah, Wahdaniah (Jambura Nursing Journal, 2024)
Background: Diabetes Mellitus (DM) is a metabolic disease characterized by hyperglycemia. As the number of DM increases, the incidence of diabetic ulcers will also increase. Approximately 14-24% of diabetic foot ulcer patients require amputation with 50% recurrence after three years. This may be due to a lack of knowledge and information in carrying out foot care independently. Most DM patients still think that all they need to do is control their blood glucose levels, so they pay less attention to the condition or cleanliness of their feet, don't wear sandals, and don't cut their nails properly, which creates a risk of recurring wounds. The research aims to determine the effect of providing Diabetic Self Foot Care (DSFC) health education on patient knowledge and attitudes about preventing diabetic foot ulcers. Method: This research was a descriptive-analytical design with a pretest–posttest cross-sectional study approach. Sampling in this research used a total sampling technique, obtaining a sample of 15 respondents. Data collection used measuring instruments in the form of questionnaires, data analysis uses the non-parametric statistical test Wilcoxon Sign Test. Results: The results of respondents' measurements after being given education about preventing diabetic foot ulcers showed that 15 of the respondents had a positive attitude after being given the education. The results of the analysis through statistical tests were obtained by Asymp.Sig. (2-tailed) 0.001 which means it is smaller than the p-value 0.05, so the result is